Options, futures, and other derivatives - Hull, John (Pearson Education, 2015)
Revised edition of the author's Options, futures, and other derivatives, [2015].; Includes bibliographical references and indexes.; Preface -- Introduction -- Futures markets and central counterparties -- Hedging strategies using futures -- Interest rates -- Determination of forward and futures prices -- Interest rate futures -- Swaps -- Securitization and the credit crisis of 2007 -- XVAS -- Mechanics of options markets -- Properties of stock options -- Trading strategies involving options -- Binomial trees -- Wiener processes and ito? 's lemma -- The black/scholes/merton model -- Employee stock options -- Options on stock indices and currencies -- Futures options -- The greek letters -- Volatility smiles -- Basic numerical procedures -- Value at risk and expected shortfall -- Estimating volatilities and correlations -- Credit risk -- Credit derivatives -- Exotic options -- More on models and numerical procedures -- Martingales and measures -- Interest rate derivatives : the standard market models -- Convexity, timing, and quanto adjustments -- Equilibrium models of the short rate -- No-arbitrage models of the short rate -- Hjm, lmm, and multiple zero curves -- Swaps revisited -- Energy and commodity derivatives -- Real options -- Derivatives mishaps and what we can learn from them -- Author index -- Subject index.